PERUBAHAN UPACARA KEMATIAN SAYUR MATUA DALAM ETNIS SIMALUNGUN DI DESA SONDI RAYA - Elvera Chrismiseri Purba; Pulung Sumantri (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2020)
Research title